Phytobezoar: A Brief Report with Surgical and Radiological Correlation - Sameer A. Hirji; Faith C. Robertson; Grace F. Chao; Bharti Khurana; Jonathan D. Gates (Case Reports in Surgery)
Gastrointestinal bezoars, collections of incompletely digested material within the alimentary tract, can present as a diagnostic challenge and should be considered in the differential diagnosis and management of small bowel obstruction, ischemic bowel, or bowel perforation. We present a case of a 37-year-old man with a distant history of laparotomy for superior mesenteric artery thrombosis requiring partial small bowel resection of the jejunum who presented with worsening abdominal pain, nausea, vomiting, and hematemesis. An abdominal computed tomography revealed dilated loops of small bowel with a transition point at the ileum, distal to his prior bowel anastomosis. He was managed initially nonoperatively, but persistent vomiting and worsening distention necessitated urgent exploratory laparotomy. During the procedure, a 4 cm by 3 cm phytobezoar was discovered at the midjejunum. The patient had an unremarkable postoperative course with no further symptoms at 1-year follow-up. Timely diagnosis and treatment of bezoar is essential to minimize patient complications.